Demographic and seasonal characteristics of respiratory pathogens in neonates and infants aged 0 to 12 months in the Central‐East region of Tunisia. Issue 4 (21st November 2018) - Brini Khalifa, Ines; Hannachi, Naila; Guerrero, Aida; Orth‐Höller, Dorothea; Bhiri, Sana; Bougila, Jihene; Boughamoura, Lamia; Merchaoui, Sonia Nouri; Sboui, Hassen; Mahdhaoui, Nabiha; Schiela, Britta; Laer, Dorothee Holm‐von; et al.
Abstract : Background: This study aimed to characterize the epidemiology of pathogenic respiratory agents in patients aged 0 to 12 months and hospitalized for acute respiratory infections in Tunisia between 2013 and 2014. Methods: A total of 20 pathogens, including viruses, Mycoplasma pneumoniae, and Streptococcus pneumoniae, were detected using molecular sensitive assays, and their associations with the patient's demographic data and season were analyzed. Results: Viral infectious agents were found in 449 (87.2%) of 515 specimens. Dual and multiple infectious agents were detected in 31.4% and 18.6% of the samples, respectively. Viral infection was predominant in the pediatric environment (90.8%, P < 0.001), male patients (88.0%), and spring (93.8%). Rhinovirus was the most detected virus (51.8%) followed by respiratory syncytial virus A/B (34.4%), coronavirus group (18.5%), adenovirus (17.9%), and parainfluenza viruses 1‐4 (10.9%). Respiratory Syncytial virus A/B was significantly associated with gender (38.0% male cases vs 28.3% female cases, P = 0.02). Infections by Adenovirus, Bocavirus, and Metapneumovirus A/B increased with increasing age of patients (predominated cases aged 6‐12 months, P < 0.001). S. pneumoniae was detected in 30.9% of th tested samples. In 18.2% of the negative viral infections, only S. pneumoniae was identified. Conclusion: A predominance of the rhinovirus infection was observed in this study. Coronavirus subtypes were described for the first time in Tunisia. The observed different pathogenic profiles across age groups could be helpful to avoid the misclassification of patients presenting with ARIs at the triage level when no standardized protocol is available. This study will provide clues for physicians informing decisions regarding preventive strategies and medication in Tunisia. Abstract : This study provides a useful starting point for a better understanding about the circulation of respiratory infectious agents in the area of Sousse, Tunisia. It will participate to reduce the overuse of unnecessary antibiotics in public hospitals which will avoid bacterial resistance and contribute to the implementation of preventive strategies and control systems in Tunisia.